The long way back : a novel - Baart, Nicole (Atria Paperback, 2023)
When her daughter goes missing right before her high school graduation, social media star Charlie, suspected of foul play by their fans, the police and the FBI, realizes the rosy façade they portrayed online hid a dangerous reality as she searches for the daughter she thought she knew.